(untitled) (International Journal of Food and Nutritional Sciences, 2020)
Organizations with strong learning cultures are better able to develop new products, ideas and concepts than those without such an orientation. They are more adaptable in response to changing conditions–whether arising as a result of natural disasters or from competition with other businesses. And this in turn leads to improved long-term company performance. Green innovation refers to the development of environmentally sound products and processes. Sustainable business practices are defined as integrating environmental and social concerns into strategy and operations (such as increasing resource efficiency, labor fairness, or responsible governance). These practices help companies reduce risks, lower costs; attract both customers and talent; and enhance their reputation. Taken together, this can lead to higher profits as well as a more resilient future. It is shown by the survey that all of these aspects are positive for sustainable business performance. Moreover, the three elements are interrelated: Learning culture breeds good green innovation and operation programmed, as well as sustainable behavior. At the same time green behaviors promote learning and innovation: they are indeed quite the pair! Companies that have a learning culture, invest in green innovation and put sustainable business practices into everyday operations are liable to achieve superior performance not only in financial terms but also by all the standards for environmental and social sustainability. Study survey was conducted among 202 respondents from the manufacturing organizations to know the role and impact of Learning Orientation, Green Innovations, and Sustainable Business Practices on Sustainable Firm Performance. The study concludes that there are significant Impact of Learning Orientation, Green Innovations, and Sustainable Business Practices is found on Sustainable Firm Performance.